Síntese de complexos de Mg(II), atividade antioxidante e citotóxica - Santos, Josenilton de Jesus (Universidade Federal de São Carlos, 2021)
The objective of this work was to develop metal complexes containing natural products that have antioxidant activity to be applied in the cosmetics sector. For that, 3 [Mg(phen)2PN]+ metal complexes were synthesized and characterized, where phen = 1,10-phenanthroline and PN are the natural products: caffeic acid (caf), cinnamic (cin) and cinnamic 4-dimethylamino acid (dmaca). The characterizations of ligands and complexes were carried out by electron injection mass spectrometry, UV-Vis, infrared, and 1H NMR spectroscopic techniques. The antioxidant activity of the compounds was investigated in relation to electron and hydrogen atom transfer using the free radical DPPH. In these experiments, only free caffeic acid and its [Mg(phen)2(caf)]+ complex showed antioxidant activity in relation to DPPH. An indirect test to determine the ability of superoxide dismutase (SOD) to inhibit the reactions induced by the superoxide radical anion was performed. Using the riboflavin reduction method in the presence of methionine and induced by 420 nm light irradiation, the antioxidant capacity of the complexes in relation to the superoxide radical was evaluated. In this study, antioxidant activity was observed for the phenolic compounds caffeic acid (caf) and cinnamic 4-dimethylamino acid (dmaca), as well as for their respective [Mg(phen)2(caf)]+ and [Mg(phen)2(dmaca)]+ complexes, with the highest inhibition percentages of O2.- were observed for the complexes. The antioxidant activity in relation to singlet oxygen (1O2) was performed using the paramagnetic resonance (EPR) technique. For the [Mg (phen)2(caf)]+ complex the IC50 value was 5.0 μg mL-1 and for the [Mg(phen)2(dmaca)]+ the IC50 value was 7.5 μg mL-1. The complexes did not inhibit the activity of the enzyme acetylcholinesterase. MTT assays to estimate the cytotoxicity of complexes in A375 human melanoma cells indicated IC50 around 6 μM for the 3 complexes studied.
Synthesis of Mg(II) complexes, antioxidant and cytotoxic activity
Keywords: Atividade antioxidante; Fotoprotetor; Magnésio; Antioxidant activity; Photoprotector; Magnesium; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA